Lipidomics Revealed Alteration of Sphingolipid Metabolism During the Reparative Phase After Myocardial Infarction Injury - Hua, Tong; Bao, Qiankun; He, Xue; Cai, Wenbin; He, Jinlong (Frontiers in Physiology, 2021)
Aberrant sphingolipid metabolism contributes to cardiac pathophysiology. Emerging evidence found that an increased level of ceramide during the inflammatory phase of post-myocardial infarction (MI) served as a biomarker and was associated with cardiac dysfunction. However, the alternation of the sphingolipid profile during the reparative phase after MI is still not fully understood. Using a mouse model of the left anterior descending ligation that leads to MI, we performed metabolomics studies to assess the alternations of both plasma and myocardial sphingolipid profiles during the reparative phase post-MI. A total number of 193 sphingolipid metabolites were detected. Myocardial sphingolipids but not plasma sphingolipids showed marked change after MI injury. Ceramide-1-phosphates, which were accumulated after MI, contributed highly to the difference of sphingolipid profiles between groups. Consistently, the expression of ceramide kinase, which phosphorylates ceramides to generate ceramide-1-phosphates, was upregulated in heart tissue after MI injury. Our findings revealed that the altering sphingolipid metabolism during the reparative phase post-MI, and highlighted the potential role of ceramide kinase/ceramide-1-phosphate in ischemic heart disease.